Spiro annulation of cage polycycles via Grignard reaction and ring-closing metathesis as key steps - Kotha, Sambasivarao; Saifuddin, Mohammad; Ali, Rashid; Sreevani, Gaddamedi (Beilstein Journal of Organic Chemistry, 2015)
A simple synthetic strategy to C2-symmetric bis-spiro-pyrano cage compound 7 involving ring-closing metathesis is reported. The hexacyclic dione 10 was prepared from simple and readily available starting materials such as 1,4-naphthoquinone and cyclopentadiene. The synthesis of an unprecedented octacyclic cage compound through intramolecular Diels–Alder (DA) reaction as a key step is described. The structures of three new cage compounds 7, 12 and 18 were confirmed by single crystal X-ray diffraction studies.
Keywords: cage molecules; Diels–Alder reaction; Grignard reaction; ring-closing metathesis; spirocycles